Photogrammetric mapping based on UAV imagery - Berteška, Tautvydas; Ruzgienė, Birutė (Geodesy and Cartography, 2013)
Unmanned Aerial Vehicle (UAV) and Digital Photogrammetry is an up-to-date area mapping technology. Implemented features are low-cost, mobile and simple. UAV (fixed-wing EPP-FPV) with mounted digital camera (Canon S100) was used for imagery while digital photogrammetry processing (with lisa software application) was applied for cartographic data collection. High imagery quality is a significant factor for the efficiency and quality of standard mapping products, such as Digital Elevation Model and Ortho Images. DEM and Orthophoto quality mainly depends on camera resolution, flight height and accuracy of Ground Control Points (GCP). In experimental investigations, GCP coordinates were gained interactively from the Internet. Application of the appropriate DEM checking technique showed that DEM error was up to 0.5 m.